Program of collaborative digital tools to strengthen the academic performance of students in early childhood education - Troya Félix, Hugo Enrique (2025)
The purpose of this study was to test the effectiveness of a program based on collaborative digital tools to enhance the academic performance of students of the Early Childhood Education career at an Ecuadorian university during 2025. The research is framed in the use of digital technologies in education, contributing to the fulfillment of Sustainable Development Goal 4 (SDG 4), aimed at guaranteeing equitable access to innovative pedagogical resources and the development of competencies of the 21st century. A longitudinal quasi experimental design with a quantitative approach was applied, forming an experimental group and a control group in a sample of 140 students. The variables analyzed were cognitive, attitudinal and procedural performance, evaluated by survey. The findings showed that, after the intervention, 85.7% of the participants in the experimental group achieved a high level of cognitive performance, compared to 18.6% in the control group. These results reflect significant progress in learning thanks to the use of digital tools. In conclusion, the collaborative digital tools program proved to be highly effective in improving academic performance and favoring the development of essential competencies in initial teacher training in higher education institutions.